Peningkatan Mutu Pendidikan Melalui Pengembangan Budaya Lokal - Fathimah M.Zen; Djafar Umar (Jurnal Ilmiah Wahana Pendidikan, 2023)
Local culture is a treasure trove of Indonesian artistic treasures, some of which are known throughout the world. In the world of education, local culture is also used as a medium in the learning process. Therefore, education cannot be separated from cultural development because it is closely related. This paper aims to describe the relationship between education and the existence of culture and tries to explain the correlation descriptively which is supported by the opinion of experts. The results of the analysis based on theory and reality in the field show that local culture is able to provide a very good stimulus in efforts to improve the quality of education. Because local culture can be used as a medium for creating learning materials by way of field practice through dance, oral literature, local wisdom (culinary), the implementation of which is in the form of field visits or to tourist attractions to practice it. Thus, this will encourage students to be enthusiastic in absorbing and easily understanding it.